PENGARUH PELATIHAN TERHADAP PENGETAHUAN TENTANG GIZI BURUK DAN INTERPROFESSIONAL COLLABORATION PETUGAS PUSKESMAS - Risnah Risnah; Rosmah Rosmah; Mustamin Mustamin; Imam Sofingi (Universitas Islam Negeri Alauddin Makassar, 2018)
Very complex health problems require treatment involving all health professionals. The nutritional status of children is one of the important things to prepare a quality generation. Health education in the form of training is expected to change the competence of collaboration across healthcare professionals. The aim of the study was to determine the effect of training on health workers on knowledge about malnutrition and collaboration across professions. This study uses a Mix-Method approach with triangulation techniques using a questionnaire for qualitative stages by conducting a content analysis and on a quantitative stage using the research design method